Scorpion venoms and associated toxins as anticancer agents: update on their application and mechanism of action. - Rivas Caceres, Raymundo Rene (2020)
Cancer remains one of the deadliest non-infectious diseases of the 21st century, causing millions of mortalities per year worldwide. Analyses of conventional treatments, such as radiotherapy and chemotherapy, have shown not only a lower therapeutic efficiency rate but also plethora of side-effects. Considering the desperate need to identify promising anticancer agents, researchers are in quest to design and develop new tumoricidal drugs from natural sources. Over the past few years, scorpion venoms have shown exemplary roles as pivotal anticancer agents. Scorpion venoms associated metabolites, particularly toxins demonstrated in vitro anticancer attributes against diversified cell lines by inhibiting the growth and progression of the cell cycle, inhibiting metastasis by blocking ion channels such as K+ and Cl−, and/or inducing apoptosis by intrinsic and extrinsic pathways. This review sheds light not only on in vitro anticancer properties of distinct scorpion venoms and their toxins, but also on their mechanism of action for designing and developing new therapeutic drugs in future.